2022
DOI: 10.1111/jcmm.17254
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPC regulates RhoA to induce DNA damage repair and cancer‐associated fibroblast activation causing radiation resistance in pancreatic cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…A critical gene for DNA double-strand break repair, Brca1 (BRCA1 DNA Repair Associated) [ 66 ], had a 2.71-fold decrease in expression by the end of lactate adaptation. The gene with the greatest net downregulation, Hnrnpc (Heterogeneous Nuclear Ribomucleoprotein C), is a regulator of pre-mRNA processing and has been observed to be overexpressed in some cancers; however, a reduced expression of Hnrnpc has been shown to limit tumor proliferation [ 67 , 68 ]. Genes with a net differential expression change are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A critical gene for DNA double-strand break repair, Brca1 (BRCA1 DNA Repair Associated) [ 66 ], had a 2.71-fold decrease in expression by the end of lactate adaptation. The gene with the greatest net downregulation, Hnrnpc (Heterogeneous Nuclear Ribomucleoprotein C), is a regulator of pre-mRNA processing and has been observed to be overexpressed in some cancers; however, a reduced expression of Hnrnpc has been shown to limit tumor proliferation [ 67 , 68 ]. Genes with a net differential expression change are shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of HNRNPC has been observed in lung cancer, breast cancer, and oral squamous cell carcinoma patients ( 3436 ). This gene has been shown to regulate tumor cell proliferation and promote radiation resistance in pancreatic cancer ( 37 ) and mediate mRNA stabilization to alter energy metabolism, facilitating metastasis and invasion of oral cancer cells ( 38 ). Collectively, these findings suggested that the top genes revealed by MitoTracer analysis may play a role in primary BRAF-inhibitor resistance and represent potential targets for reversing resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, A549 cells had weakened migration in response to the treatment with the Rho inhibitor CT04 [ 19 ]. Moreover, RhoA inhibition weakened the activity of cancer-related fibroblasts and overcame radiation resistance in pancreatic cancer [ 27 ]. Further studies are also essential to verify whether the interplay between CX3CL1/CX3CR1 and the RhoA signaling was also involved in the resistance to other chemotherapeutic agents and other types of cancers.…”
Section: Discussionmentioning
confidence: 99%